Inverse association between type 2 diabetes and aortic root dimension in hypertensive patients. (1st February 2017) - Nardi, Emilio; Mulè, Giuseppe; Nardi, Chiara; Geraci, Giulio; Averna, Maurizio
Abstract: Background: Some data support the concept that aortic root diameter (ARD) in hypertension may be regarded as a marker of subclinical organ damage. The impact of type 2 diabetes mellitus (DM) on cardiac structure and function is known, although the relationship between DM and ARD is not clear. The aim of our study was to evaluate the influence of DM on ARD in hypertensive patients. Methods: We enrolled 1693 hypertensive patients (aged 63.7 ± 9.6 years). The population was divided into two groups: the first one with DM ( n = 747) and the second one without DM ( n = 946). ARD was measured by echocardiography at level of Valsalva's sinuses using echocardiography M-mode tracings. It was considered as absolute measure and normalized to height (ARD/H) and body surface area (ARD/BSA). Left ventricular mass index (LVMI) and some parameters of systolic and diastolic function have been valued by means of echocardiography and tissue Doppler imaging. Results: The DM group was characterized by more elevated values of LVMI and a worst systolic and diastolic function. ARD value was significantly lower in DM group in comparison to patients without DM only when indexed for BSA (ARD/BSA = 18.7 ± 2.3 mm/m 2 vs 18.3 ± 2.0 mm/m 2, p = 0.01). This difference remained statistically significant, even after correction by age, sex and BMI ( p = 0.01). A multivariate linear regression analysis demonstrated an inverse relationship between DM and ARD/BSA after correction for potential confounders (β = 0.10, p < 0.001). Conclusions: Our results confirm the hypothesis of a protective role of DM on aortic root dilatation.